The Toponyms of a Big City: an Informal Aspect (on Materials of Kharkiv) - Удовенко, Лідія (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2019)
The article deals with the unofficial names of the streets of Kharkiv. Until 1804 in Kharkiv, all street names were unofficial. Many streets had two or three names. These names were known only to local residents. From the colloquial speech of the townspeople, the city government chose one name, and that name became the official name. Informal names of urban sites best convey the opinion of citizens about their city. In historical toponymy, informal names can be an argument in discussions about how to measure the area of ​​a city. In local lore literature data on the area of ​​the same city sometimes differ significantly. The process of the unofficial name of urban objects has been and remains spontaneous. Informal names are influenced by the interaction of languages, the emergence or disappearance of a certain concept, the natural or unnatural loss of the meaning of a city object, the archaization of names, the literary and artistic activity. One of the objectives of the article is to determine the cause of the appearance of groups of informal names of urban objects and to determine the peculiarities of informal names in the city. The factors affecting the process of the emergence of informal names are listed. The analysis of urbonyms and the processes of creating an informal nomination is combined with the study of the linguistic specifics of the names of streets and other objects of a large city. The author of the article talks about the future directions for the study of unofficial names in the city. Scientists studying urbonyms should take into account the informal names of city objects, colloquial forms of names, features of youth slang, the influence of slang on the formation of urbonyms and of urban identity.